Ectomycorrhizospheric Microbiome Assembly Rules of Quercus mongolica in the Habitat of SongRong (Tricholoma matsutake) and the Effect of Neighboring Plants - Yan-Ji Si; Yang Xu; Bin-Qi Li; Jin Liu; Li-Peng Meng; Yu Li; Rui-Qing Ji; Shu-Yan Liu (Diversity, 2022)
Host plants are known to determine the distribution and development of ectomycorrhizal fungi such as Tricholoma matsutake; however, we found that the fruit body distribution of T. matsutake was different in Quercus mongolica pure or mixed forests. To clarify the fungal and other microbial composition rules of host plants, ectomycorrhizal root tip samples of Q. mongolica mixed with different plants were selected for study. By using high-throughput sequencing, we obtained 5229 fungal and 38,834 bacterial amplicon sequence variants (ASVs) as determined by internally transcribed spacer ribosomal RNA (ITS rRNA) and 16S ribosomal RNA (16S rRNA) sequencing via the Illumina NovaSeq platform. Among the neighboring plants, there were no significant differences in fungal or bacterial alpha diversity, but there was a significant difference (p < 0.05) in ectomycorrhizal alpha diversity. The fungal, bacterial and ectomycorrhizal fungal communities in the ectomycorrhizosphere of Q. mongolica all showed differences in beta diversity and species composition. In addition, the physical and chemical properties of the soil and the relationships among species could affect the relative abundance of fungi, bacteria and ectomycorrhizal fungi, but the soil microbial pool had little effect on microbial composition. Using PICRUSt2, some significantly up-regulated (p < 0.05) metabolic functions in ectomycorrrhizospheric microbial communities were predicted, which would be an interesting research field for ectomycorrhizal microecology.